6a-3(a+2)=3

Simple and best practice solution for 6a-3(a+2)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-3(a+2)=3 equation:


6a-3(a+2)=3

We simplify the equation to the form, which is simple to understand
6a-3(a+2)=3

Reorder the terms in parentheses
6a+(-3a-6)=3

Remove unnecessary parentheses
+6a-3a-6=+3

We move all terms containing a to the left and all other terms to the right.
+6a-3a=+3+6

We simplify left and right side of the equation.
+3a=+9

We divide both sides of the equation by 3 to get a.
a=3

See similar equations:

| 16n-15-4n=22-8n+3 | | 7(2y-9)-(y+6)= | | 6=10x-10+3x | | x+(2x)=126 | | -36=-18x-18y | | 5z-3+2z=18 | | 2x+2=6+6x | | 3x-8(-3-6x)=24 | | 24+3x=129 | | -0.2x+0.7x-3=-8 | | 3(2x+7y)=5x+24 | | -6=m+-3.42 | | 4-5x=6-6x | | -8(1-4n)-2n= | | =369x-3x | | 0.4x-2.5=0.6 | | -2(2-8b)= | | 5y+2-3=-3y+10y | | q=wxy | | 7(7-3y)=-y-11 | | 10a^2-29a+10= | | 3p-8=12-4p | | 6(2x-1)=-6(x+3) | | x=5(2)-7 | | 8x-28=36 | | -8(8+3b)+3= | | .2(7x-6)=.25(6x-8) | | 3.33b=5 | | 3n-8=72 | | 0.384615385*t=-9 | | 2(q-5)=3(q+5) | | x*x+x=6 |

Equations solver categories